Joint inhibition of mitochondrial complex IV and alternative oxidase by genetic or chemical means represses chloroplast transcription in Arabidopsis - Adamowicz-Skrzypkowska, Aleksandra (Philos Trans R Soc Lond B Biol Sci, 2020)
Changes in the functional state of mitochondria have profound effects on other cellular compartments. Genome-wide expression analysis of Arabidopsis rps10 mutants with an RNAi-silenced expression of mitoribosomal S10 protein has revealed extensive transcriptional reprogramming. A meta-analysis comparing expression datasets of 25 mitochondrial perturbations showed a high similarity of the aox1a:rpoTmp mutant, which is defective in the alternative oxidase (AOX1a) and dual-targeted mitochondrial and plastid RNA polymerase (RPOTmp), to rps10. Both rps10 and aox1a:rpoTmp showed a significantly decreased electron flux through both the cytochrome and the alternative respiratory pathways, and a markedly decreased the expression of nuclear-encoded components of the chloroplast transcription machinery. In line with this, a decreased level of plastid transcripts was observed in rps10 and aox1a:rpoTmp, which was reflected in a reduced rate of chloroplast transcription. Chemical treatment of wild-type seedlings with respiratory inhibitors showed that only simultaneous and direct inhibition of complex IV and AOX activity decreased the level of plastid transcripts. Taken together, both chemical and genetic studies show that the limitation of the activity of two mitochondrial terminal oxidases, complex IV and AOX, negatively impacts chloroplast transcription. Salicylic acid and oxygen are discussed as putative mediators of the signalling pathway between mitochondria, nucleus and chloroplasts. This article is part of the theme issue ‘Retrograde signalling from endosymbiotic organelles’.